Implementasi Model Pembelajaran Kooperatif Team Accelerated Instruction untuk Meningkatkan Hasil Belajar Akuntansi Siswa SMA - Tunisa, Juhro (Universitas Pendidikan Ganesha, 2022)
This study aims to improve student’s of class XII IPS1 SMA Negeri 1 Tirtayasa academic year of 2021/2022 with implementation Cooperative Learning Method Type Team Accelerated Instruction (TAI). The data collection techniques used in this research were test and documentation. The including instrument used in this research are test and field note. The data analysis technique in this research was quantitative descriptive data analysis. Based on the research result, on the cycle I, the average score of accounting learning outcome in the pretest was 44,33 while in the post test, the average score was 82,11 or increased 37,78 or 85,22%. On the cycle II, the average score of accounting learning outcome in the pretest was 48,89, while the post test, the average score was 91,11 or increased 42,22 or 86,36%. On the cycle I, the student’s accounting learning outcome completeness increased from 5,56% on the pretest to 63,89% on the posttest or increased 58,33%. On the cycle II, the student’s accounting learning outcome completeness increased from 11,11% of pretest to 86,11% on the posttest or increased 75,00% based on the result, hypothesis of action on this research is accepted.